Soil degradation regulates the effects of litter decomposition on soil microbial nutrient limitation: Evidence from soil enzymatic activity and stoichiometry - Li, Jianan; Niu, Ximei; Wang, Ping; Yang, Jingjing; Liu, Jinwen; Wu, Donghui; Guan, Pingting (Frontiers in Plant Science, 2023)
Soil microorganisms could obtain energy and nutrients during litter decomposition with the help of soil extracellular enzymes. The litter types were among the most critical factors that affect soil extracellular enzyme activities. However, how litter types modulate the soil extracellular enzyme activity with grassland gradation is unclear. Here, we conducted a 240-day experiment of two different types of litter decomposition on soil extracellular enzyme activity and stoichiometry in different degraded grasslands. We found that C-acquiring enzyme activity and the enzyme stoichiometry of C/N were higher in Chloris virgata litter than in Leymus chinensis litter at lightly degraded level and C-acquiring enzyme activity in C. virgata was 16.96% higher than in L. chinensis. P-acquiring enzyme activity had the same trend with litter types in moderately and highly degraded levels and it was 20.71% and 30.89% higher in C. virgata than that in L. chinensis, respectively. The change of the enzyme stoichiometry with litter types was only showed in the enzyme stoichiometry of C/N at lightly degraded level, suggesting that litter types only affected the microbial C limitation in lightly degraded grassland. Almost all soil extracellular enzyme activities and extracellular enzyme stoichiometry, except the enzyme stoichiometry of N/P, decreased with grassland degraded level increasing. All vector angles were less than 45° suggesting that soil microorganisms were limited by N rather than by P during the decomposition process. Enzyme vector analysis revealed that soil microbial communities were co-limited by C and N during litter decomposition. Moreover, based on Random Forest (explaining more than 80%), we found that soil total nitrogen, total carbon, total phosphorus, dissolved organic C, pH and EC were important factors affecting soil enzyme activities by degradation levels. Our results emphasized that degradation levels could modulate the influences of litter types on soil extracellular enzyme activity. Our study enhanced our understanding in resource requirements for microbial communities to litter resources in degraded grassland and helped us to provide new ideas for improving degraded grassland ecosystems.